National Food Systems Summit Dialogues in Viet Nam incorporate A4NH evidence around food safety as part of the United Nation Food Systems Summit - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The national Dialogues helped Member States to develop pathways towards safe and sustainable food systems and solicit expressions of intent to support these pathways from a broad range of stakeholders.